Urban Wage Premia, Cost of Living, and Collective Bargaining - Marianna Belloc; Paolo Naticchioni; Claudia Vittori (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we estimate the urban wage premia (UWP) in Italy, with its economy characterized by the interplay between collective bargaining and spatial heterogeneity in the cost of living. We implement a reduced-form regression analysis using both nominal and real (in temporal and spatial terms) wages. Our dataset for the 2005-2015 period includes, for workers' characteristics, unique administrative data provided by Italian Social Security Institute and, for the local CPI computation, housing prices collected by Italian Revenue Agency. For employees covered by collective bargaining, we find a zero UWP in nominal terms and a negative and non-negligible UWP in real terms (-5%). To capture the role played by centralized wage settings, we also consider various groups of self-employed workers, who are not covered by national labour agreements, while living in the same locations and enjoying the same amenities as employees. We find that the UWP for self-employed workers are up to 25 times greater than for employees. Moreover, sorting proves more notable in the case of self-employed workers, i.e. the larger UWP provide the higher incentives for high-skilled individuals and better firms to locate in cities. Our findings are confirmed on extending the analysis along the wage distribution.
Keywords: R12; R31; J31; 330; urban wage premium; cost of living; collective bargaining